Corundum mullite brick for nuclear fuel high-temperature sintering furnace and preparation method of corundum mullite brick
By using specific components of electromelted white corundum and mullite, combined with aluminum dihydrogen phosphate and yttrium oxide, corundum mullite bricks with excellent high temperature resistance, thermal shock resistance and chemical corrosion resistance were prepared, which solved the problem of insufficient performance of existing refractory bricks in the high-temperature sintering process of nuclear fuel, and significantly improved the safety and quality of the sintering process.
Patent Information
- Application Number
- CN202411942982.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
Existing refractory bricks are prone to softening, deforming or melting during high-temperature sintering of nuclear fuel, and are insufficient in thermal shock resistance and chemical corrosion resistance, which affects the quality and safety of nuclear fuel sintering.
Using specific components of electromelted white corundum and mullite as the main raw materials, combined with aluminum dihydrogen phosphate as the binder and yttrium oxide as the additive, a stable crystal structure is formed by high-temperature sintering to prepare corundum mullite bricks with excellent high temperature resistance, thermal shock resistance and chemical corrosion resistance.
The brick maintains structural stability in extremely high temperature environments, prevents softening and deformation, significantly improves thermal shock resistance and chemical corrosion resistance, extends service life, and improves the quality and safety of nuclear fuel sintering.
Smart Images

Figure BDA0005212974490000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of nuclear fuel high temperature sintering furnaces, in particular to a corundum mullite brick for a nuclear fuel high temperature sintering furnace and a preparation method thereof. Background Art
[0002] In the field of high-temperature sintering furnaces for nuclear fuel, corundum mullite bricks are a key refractory material. The high-temperature sintering process of nuclear fuel needs to be carried out in extreme temperature, radiation and chemical environments, which places extremely high requirements on the performance of refractory materials.
[0003] On the one hand, the high temperature resistance of existing refractory bricks is insufficient. During the sintering process of nuclear fuel, the temperature is often as high as thousands of degrees Celsius. Some existing refractory bricks are prone to softening, deformation or even melting under long-term high temperature, which cannot meet the requirements of long-term stable operation of nuclear fuel high-temperature sintering furnaces. On the other hand, the thermal shock resistance is poor. During the sintering process of nuclear fuel, the temperature changes frequently and violently. Refractory bricks need to frequently withstand the thermal stress caused by sudden temperature changes. Existing refractory bricks are prone to cracks under such thermal shock, which in turn affects their service life and the sealing of the furnace body. In addition, the resistance of existing refractory bricks to chemical erosion is limited. Nuclear fuel and its reaction products may have strong chemical corrosion, which will corrode the internal structure of refractory bricks, causing their performance to gradually decline, affecting the quality and safety of nuclear fuel sintering. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a corundum mullite brick for a nuclear fuel high-temperature sintering furnace and a preparation method thereof, which solves the problem that the existing refractory bricks have limited resistance to chemical erosion, and that nuclear fuel and its reaction products may have strong chemical corrosiveness, which will corrode the internal structure of the refractory bricks, causing their performance to gradually decline, affecting the quality and safety of nuclear fuel sintering.
[0005] To achieve the above purpose, the present invention is implemented by the following technical scheme: The corundum mullite brick for nuclear fuel high temperature sintering furnace includes the following raw materials by weight:
[0006] 60-70 parts of fused white corundum, wherein the particle size of the fused white corundum is 3-5 mm;
[0007] 30-40 parts of mullite, wherein the particle size of the mullite is 1-3 mm;
[0008] 5 to 8 parts of a binder, wherein the binder is aluminum dihydrogen phosphate (Al(H2PO4)3);
[0009] 3 to 5 parts of an additive, wherein the additive is yttrium oxide.
[0010] Preferably, the main component of the fused white corundum is aluminum oxide (Al2O3), and the content thereof is ≥99%.
[0011] Preferably, the mullite is composed of Al2O3 and SiO2, wherein the content of Al2O3 is 70-75%, and the content of SiO2 is 25-30%.
[0012] Preferably, the content of Al2O3 in the aluminum dihydrogen phosphate is 30-35%, and the content of P2O5 is 60-65%.
[0013] The method for preparing alumina-mullite bricks for a nuclear fuel high-temperature sintering furnace comprises the following steps:
[0014] Step 1: Add fused white corundum, mullite, binder and additives into a mixer in proportion, and mix at a speed of 20 to 30 r / min for 1 to 2 hours to obtain a mixture;
[0015] Step 2: Add 3-5% deionized water to the mixture, stir evenly and place the mixture in an environment with a humidity of 40-60% for 12-24 hours;
[0016] Step 3: Put the trapped blank into a mold and shape it under a pressure of 100-200 MPa to obtain a brick;
[0017] Step 4: Dry the bricks at 100-150°C for 24-48 hours with a heating rate of 5-10°C / h. The dried bricks are sintered at high temperature to form bricks.
[0018] Preferably, the fused white corundum and mullite in step one are screened before adding, and the screened fused white corundum and mullite particles are dried at 120-140° C. for 1.2-1.8 hours, and the binder and additive are ground to a particle size of less than 100 μm.
[0019] Preferably, the temperature of the deionized water added in step 2 is 25-30°C, the stirring speed is 60-70 r / min, the stirring time is 20-25 minutes, and the humidity of the trapped environment is 45-55% and the temperature is 22-28°C.
[0020] Preferably, the specific steps of drying the bricks in step 4 are:
[0021] Place the bricks in a drying oven and pre-dry them at 40-60°C for 2-4 hours to remove some moisture from the surface of the bricks. Then heat them to 100-150°C at a heating rate of 5-10°C and dry them at this temperature for 24-48 hours.
[0022] Preferably, the high temperature sintering in step 4 is carried out in a high temperature sintering furnace under a reducing atmosphere, and the volume fraction of hydrogen in the reducing atmosphere is 5-10%.
[0023] Preferably, the sintering process in the high temperature sintering furnace is divided into three stages:
[0024] In the first stage, the temperature is raised to 800-1000°C at a heating rate of 50-80°C / h and kept at this temperature for 2-4 hours to allow the raw material particles to initially undergo a solid phase reaction;
[0025] In the second stage, the temperature is raised to 1300-1500°C at a heating rate of 80-120°C / h and kept at this temperature for 4-6 hours to promote crystal growth and structural densification;
[0026] In the third stage, the temperature is raised to 1600-1800°C at a heating rate of 50-80°C / h and kept warm for 24-48 hours to allow the brick to reach its final high performance state.
[0027] The present invention provides a corundum mullite brick for a nuclear fuel high temperature sintering furnace and a preparation method thereof. It has the following beneficial effects:
[0028] 1. The present invention uses special fused white corundum and mullite as the main raw materials, combined with aluminum dihydrogen phosphate binder and yttrium oxide additive, and forms a stable crystal structure after high-temperature sintering, so that the corundum mullite brick can maintain good structural stability in the extremely high temperature environment of the nuclear fuel high-temperature sintering furnace, effectively prevent softening, deformation and melting, and ensure the smooth progress of the nuclear fuel sintering process.
[0029] 2. The corundum-mullite brick of the present invention is not easy to crack, which significantly improves its thermal shock resistance, prolongs its service life, reduces the furnace maintenance and shutdown time caused by brick damage, and improves production efficiency. During long-term use, it can effectively prevent the erosion of the internal structure of the brick by chemical substances, ensure the stability of the brick performance, thereby improving the quality and safety of nuclear fuel sintering, and reducing the safety risks such as nuclear leakage caused by damage to refractory materials. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] The embodiment of the present invention provides a corundum-mullite brick for a nuclear fuel high-temperature sintering furnace.
[0032] As one aspect of the present invention, the present invention provides a corundum mullite brick for a nuclear fuel high temperature sintering furnace, which comprises the following raw materials in parts by weight:
[0033] 60-70 parts of fused white corundum, wherein the particle size of the fused white corundum is 3-5 mm, and the main component is aluminum oxide (Al2O3), and the content is ≥99%;
[0034] 30-40 parts of mullite, wherein the mullite is composed of Al2O3 and SiO2, wherein the content of Al2O3 is 70-75%, the content of SiO2 is 25-30%, and the particle size of the mullite is 1-3 mm;
[0035] 5 to 8 parts of a binder, wherein the binder is aluminum dihydrogen phosphate (Al(H2PO4)3), wherein the content of Al2O3 is 30 to 35%, and the content of P2O5 is 60 to 65%;
[0036] 3 to 5 parts of an additive, wherein the additive is yttrium oxide.
[0037] As another aspect of the present invention, the preparation method of the above-mentioned corundum mullite brick for nuclear fuel high temperature sintering furnace is as follows, comprising the following steps:
[0038] Step 1, adding fused white corundum, mullite, a binder and an additive into a mixer in proportion, mixing at a speed of 25 r / min for 1.5 hours to obtain a mixture, wherein the fused white corundum and mullite are screened before adding, and the screened fused white corundum and mullite particles are dried at 130° C. for 1.5 hours, and the binder and the additive are ground to a particle size of less than 100 μm;
[0039] Step 2: Add 4% deionized water to the mixture, the temperature of the added deionized water is 28°C, the stirring speed is 65r / min, the stirring time is 22 minutes, and after stirring evenly, the mixture is trapped in an environment with a humidity of 50% and a temperature of 25°C for 18 hours;
[0040] Step 3: Put the trapped blank into a mold and shape it under a pressure of 150MPa to obtain a brick;
[0041] Step 4: Dry the green bricks at 120°C for 36 hours, put the green bricks into a drying oven, pre-dry them at 50°C for 3 hours to remove some moisture on the surface of the green bricks, then heat them to 130°C at a heating rate of 8°C, and dry them at this temperature for 36 hours. The dried green bricks are sintered at high temperature to form bricks. The high-temperature sintering is carried out in a high-temperature sintering furnace under a reducing atmosphere. The volume fraction of hydrogen in the reducing atmosphere is 8%. The sintering process in the high-temperature sintering furnace is divided into three stages:
[0042] In the first stage, the temperature was raised to 900°C at a heating rate of 65°C / h and kept at this temperature for 3 hours to allow the raw material particles to undergo a preliminary solid-phase reaction;
[0043] In the second stage, the temperature was raised to 1400°C at a heating rate of 100°C / h and kept at this temperature for 5 hours to promote crystal growth and structural densification;
[0044] In the third stage, the temperature is raised to 1700°C at a heating rate of 65°C / h and kept at this temperature for 32 hours, so that the brick body reaches the final high-performance state.
[0045] In order to better illustrate the implementation scheme of the corundum mullite brick for nuclear fuel high temperature sintering furnace of the present invention, the following examples are given:
[0046] Embodiment 1:
[0047] According to weight, accurately weigh 65 parts of fused white corundum, the particle size of which is 3-5mm, and the main component is aluminum oxide (Al2O3) with a content of ≥99%. The fused white corundum is screened to remove impurities and particles that do not meet the particle size requirements, and then dried at 130℃ for 1.5 hours to remove moisture and ensure the purity and performance of the raw materials.
[0048] Weigh 35 parts of mullite with a particle size of 1 to 3 mm, composed of 72% Al2O3 and 28% SiO2. Similarly, screen the mullite and dry it at 130°C for 1.5 hours; take 6 parts of aluminum dihydrogen phosphate (Al(H2PO4)3), a binder with 32% Al2O3 and 62% P2O5, and grind it to a particle size of less than 100 μm to improve dispersibility; weigh 4 parts of yttrium oxide, an additive.
[0049] The treated fused white corundum, mullite, aluminum dihydrogen phosphate binder and yttrium oxide additive are added to the mixer in proportion, and mixed at a speed of 25r / min for 1.5 hours to obtain a mixture. During the mixing process, ensure that the raw materials are fully mixed and evenly mixed so that each raw material particle can be evenly coated with the binder; add deionized water accounting for 4% of the total weight of the mixture to the mixture, the deionized water temperature is 28°C, and stir at a stirring speed of 65r / min for 22 minutes to make the water and the mixture fully contact and evenly dispersed to form a blank with a certain plasticity.
[0050] The mixed blank is placed in a sealed container and trapped for 18 hours in an environment with a humidity of 50% and a temperature of 25°C. The trapping process allows the binder to fully react with the raw materials, improves the plasticity and uniformity of the blank, and reduces defects after molding; the trapped blank is placed in a mold and molded at a pressure of 150MPa for 7 seconds to obtain a brick blank. High-pressure molding makes the blank more compact, improves the strength and density of the brick blank, and reduces defects such as pores.
[0051] The bricks were placed in a drying oven and pre-dried at 50°C for 3 hours to remove some of the moisture on the surface of the bricks. The temperature was then raised to 120°C at a heating rate of 8°C / h and dried at this temperature for 36 hours to allow the moisture inside the bricks to evaporate slowly and evenly, ensuring the structural integrity of the bricks during the drying process and fully removing the free water and some of the bound water in the bricks.
[0052] The dried bricks are placed in a high-temperature sintering furnace and sintered in a reducing atmosphere with a hydrogen volume fraction of 8%. The sintering process is divided into three stages: the first stage is to heat up to 900°C at a heating rate of 65°C / h and keep at this temperature for 3 hours to make the raw material particles undergo a preliminary solid-phase reaction; the second stage is to heat up to 1400°C at a heating rate of 100°C / h and keep at this temperature for 5 hours to promote crystal growth and structural densification; the third stage is to heat up to 1700°C at a heating rate of 65°C / h and keep at this temperature for 36 hours to make the brick reach the final high-performance state. During the entire sintering process, the heating rate and holding time are controlled to make the raw material particles fully react to form a stable crystal structure, improve the density and strength of the brick, and the reducing atmosphere is conducive to removing impurities, further improving the quality and performance of the brick.
[0053] Embodiment 2:
[0054] Prepare 60 parts of fused white corundum by weight, with a particle size of 3-5mm and an Al2O3 content of ≥99%. After screening, dry at 120℃ for 1.8 hours; 40 parts of mullite, with a particle size of 1-3mm, an Al2O3 content of 70%, and a SiO2 content of 30%. After screening, the drying conditions are the same as those of fused white corundum; 8 parts of aluminum dihydrogen phosphate binder, with an Al2O3 content of 30% and a P2O5 content of 65%, grinded to a particle size of less than 100μm; 5 parts of yttrium oxide additive.
[0055] Add the raw materials to the mixer and mix at 20r / min for 2 hours; add 25℃ deionized water accounting for 5% of the total weight of the mixture and stir at 60r / min for 25 minutes. Keep the material trapped in an environment with a humidity of 45% and a temperature of 28℃ for 24 hours; mold at 100MPa pressure and hold the pressure for 10 seconds; pre-dry at 40℃ for 4 hours, heat up to 100℃ at 5℃ / h and dry for 48 hours.
[0056] Sintering in reducing atmosphere (hydrogen gas volume fraction 5%). In the first stage, the temperature is increased to 800°C at 50°C / h and kept at this temperature for 4 hours; in the second stage, the temperature is increased to 1300°C at 80°C / h and kept at this temperature for 6 hours; in the third stage, the temperature is increased to 1600°C at 50°C / h and kept at this temperature for 48 hours.
[0057] Embodiment three:
[0058] 70 parts of fused white corundum, particle size 3-5mm, Al2O3 content ≥99%. Dry at 140℃ for 1.2 hours and then screen for use; 30 parts of mullite, particle size 1-3mm, Al2O3 content 75%, SiO2 content 25%. Drying and screening are the same as fused white corundum; 5 parts of aluminum dihydrogen phosphate binder, Al2O3 content 35%, P2O5 content 60%, grind to a particle size less than 100μm; 3 parts of yttrium oxide additive.
[0059] The raw materials were put into the mixer and mixed at 30r / min for 1 hour; 3% of the total weight and 30℃ deionized water were added and stirred at 70r / min for 20 minutes. The material was trapped at 55% humidity and 22℃ for 12 hours; 200MPa pressure molding was performed and the pressure was maintained for 5 seconds; pre-dried at 60℃ for 2 hours, and heated to 150℃ at 10℃ / h for 24 hours.
[0060] Sintering in a reducing atmosphere with a hydrogen volume fraction of 10%. In the first stage, the temperature is raised to 1000°C at 80°C / h and kept at this temperature for 2 hours; in the second stage, the temperature is raised to 1500°C at 120°C / h and kept at this temperature for 4 hours; in the third stage, the temperature is raised to 1800°C at 80°C / h and kept at this temperature for 24 hours.
[0061] Comparative Example:
[0062] 60 parts of ordinary corundum raw material (Al2O3 content of about 95%) were selected, and the particle size was not strictly screened, and the particle size distribution was between 1 and 10 mm. 35 parts of mullite raw material, Al2O3 content of about 65%, SiO2 content of about 35%, and the particle size was also not screened, ranging from 0.5 to 8 mm. 10 parts of conventional aluminate cement were used as a binder, without grinding treatment, and used directly. No special additives were added.
[0063] The above raw materials were directly added to a common mixer and mixed at a speed of 15r / min for 30 minutes. The mixing time was short and the speed was slow, so the mixing uniformity of the raw materials was poor. Ordinary tap water accounting for 6% of the total weight of the mixture was added, and the stirring speed was 40r / min for 15 minutes to form a blank. Then, the blank was trapped for 8 hours in a common environment with a humidity of about 30% and a temperature of about 15°C. The trapping time was short and the environmental humidity and temperature were not strictly controlled, so the trapping effect was not good.
[0064] The trapped blank is placed in a simple mold and formed at a relatively low pressure of 80MPa with a holding time of 3 seconds. The low molding pressure and short holding time result in a low density of the bricks. The bricks are directly placed in a natural environment to dry for 2 to 3 days. The temperature and humidity are not controlled during the drying process, and the water inside the bricks evaporates unevenly, which easily leads to cracks.
[0065] Sintering is carried out in an ordinary air atmosphere with a sintering temperature of 1500-1600°C and a heating rate of 30-50°C / h. No stage control is performed and the insulation time is 10-15 hours in total. The sintering conditions are simple and cannot effectively promote crystal growth and structure densification.
[0066]
[0067] The embodiment of the present invention has been carefully designed and strictly controlled in various links such as raw material screening and pretreatment, mixing, water mixing and trapping, molding, drying and sintering. High-purity fused white corundum and mullite with a specific composition ratio are selected, and through optimized process parameters, such as suitable raw material particle size, accurate mixing speed and time, high-quality water and reasonable process conditions, high molding pressure, gradient drying and staged sintering in reducing atmosphere, the prepared corundum mullite brick has excellent high temperature resistance, outstanding thermal shock resistance, strong chemical corrosion resistance, high product density and room temperature compressive strength. In contrast, the comparative example has poor performance in various properties due to the unscreened raw materials and random process parameters. It cannot withstand the extreme working conditions of the nuclear fuel high-temperature sintering furnace, is easy to soften and deform at high temperature, has poor thermal shock resistance, is susceptible to chemical corrosion, has low density and strength, and is difficult to meet the strict requirements of the nuclear fuel high-temperature sintering process for refractory materials, highlighting the significant advantages and importance of the preparation method of the present invention.
[0068] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. Corundum mullite bricks for high temperature sintering furnace of nuclear fuel, characterized in that: By weight, it includes the following raw materials: 60-70 parts of fused white corundum, wherein the particle size of the fused white corundum is 3-5 mm; 30-40 parts of mullite, wherein the particle size of the mullite is 1-3 mm; 5 to 8 parts of a binder, wherein the binder is aluminum dihydrogen phosphate (Al(H2PO4)3); 3 to 5 parts of an additive, wherein the additive is yttrium oxide.
2. The corundum-mullite brick for a nuclear fuel high-temperature sintering furnace according to claim 1, characterized in that: The main component of the fused white corundum is aluminum oxide (Al2O3), and the content thereof is ≥99%.
3. The corundum-mullite brick for a nuclear fuel high temperature sintering furnace according to claim 1, characterized in that: The mullite is composed of Al2O3 and SiO2, wherein the content of Al2O3 is 70-75%, and the content of SiO2 is 25-30%.
4. The corundum-mullite brick for a nuclear fuel high-temperature sintering furnace according to claim 1, characterized in that: The content of Al2O3 in the aluminum dihydrogen phosphate is 30-35%, and the content of P2O5 is 60-65%.
5. A method for preparing a corundum mullite brick for a nuclear fuel high temperature sintering furnace, using the corundum mullite brick for a nuclear fuel high temperature sintering furnace as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: Add fused white corundum, mullite, binder and additives into a mixer in proportion, and mix at a speed of 20 to 30 r / min for 1 to 2 hours to obtain a mixture; Step 2: Add 3-5% deionized water to the mixture, stir evenly and place the mixture in an environment with a humidity of 40-60% for 12-24 hours; Step 3: Put the trapped blank into a mold and shape it under a pressure of 100-200 MPa to obtain a brick; Step 4: Dry the bricks at 100-150°C for 24-48 hours with a heating rate of 5-10°C / h. The dried bricks are sintered at high temperature to form bricks.
6. The method for preparing the corundum-mullite brick for a nuclear fuel high-temperature sintering furnace according to claim 5, characterized in that: The fused white corundum and mullite in step 1 are screened before adding, and the screened fused white corundum and mullite particles are dried at 120-140° C. for 1.2-1.8 hours, and the binder and additive are ground to a particle size of less than 100 μm.
7. The method for preparing the corundum-mullite brick for a nuclear fuel high-temperature sintering furnace according to claim 6, characterized in that: The temperature of the deionized water added in step 2 is 25-30° C., the stirring speed is 60-70 r / min, the stirring time is 20-25 minutes, and the humidity of the trapped environment is 45-55% and the temperature is 22-28° C.
8. The method for preparing the corundum-mullite brick for a nuclear fuel high-temperature sintering furnace according to claim 6, characterized in that: The specific steps of drying the bricks in step 4 are as follows: Place the bricks in a drying oven and pre-dry them at 40-60°C for 2-4 hours to remove some moisture from the surface of the bricks. Then heat them to 100-150°C at a heating rate of 5-10°C and dry them at this temperature for 24-48 hours.
9. The method for preparing the corundum-mullite brick for a nuclear fuel high temperature sintering furnace according to claim 6, characterized in that: The high temperature sintering in step 4 is carried out in a high temperature sintering furnace under a reducing atmosphere, and the volume fraction of hydrogen in the reducing atmosphere is 5-10%.
10. The method for preparing the corundum-mullite brick for a nuclear fuel high temperature sintering furnace according to claim 9, characterized in that: The sintering process in the high temperature sintering furnace is divided into three stages: In the first stage, the temperature is raised to 800-1000°C at a heating rate of 50-80°C / h and kept at this temperature for 2-4 hours to allow the raw material particles to initially undergo a solid phase reaction; In the second stage, the temperature is raised to 1300-1500°C at a heating rate of 80-120°C / h and kept at this temperature for 4-6 hours to promote crystal growth and structural densification; In the third stage, the temperature is raised to 1600-1800°C at a heating rate of 50-80°C / h and kept warm for 24-48 hours to allow the brick to reach its final high performance state.
Citation Information
Patent Citations
Anti-erosion mullite brick for blast furnace and preparation method thereof
CN103641503A
High-performance modified mullite high-temperature bedplate as well as manufacturing method
CN104591753A
Corundum-mullite burnt brick applied to gas turbine combustion chamber and preparation method thereof
CN104803692A
Low-iron mullite brick and manufacturing method thereof
CN106747523A
Corundum mullite castable and preparation method thereof
CN113896514A